Visual texture agnosia in dementia with Lewy bodies and Alzheimer's disease. (June 2018) - Oishi, Yuka; Imamura, Toru; Shimomura, Tatsuo; Suzuki, Kyoko
Abstract: Background: Neuroimaging and some clinical studies have reported that the ventral visual pathway is relevant for visual texture recognition. Although a variety of visual deficits have been reported in patients with Alzheimer's disease (AD) and dementia with Lewy bodies (DLB), visual material identification and texture recognition have not been thoroughly examined. Objectives: To investigate visual texture recognition in patients with AD and DLB and to clarify the relationship between visual texture recognition and various visuoperceptual functions. Methods: Twenty-five patients with probable DLB, 53 patients with probable AD, and 32 age-matched healthy controls were included. We assessed visual texture recognition of real materials/images and visuoperceptual functions including contrast sensitivity, color perception, stereopsis, shape detection, and position in space. Results: DLB patients showed disproportionate deficits in visuoperceptual functions and visual texture recognition compared with AD patients and controls, but these dysfunctions were not correlated with each other. AD patients had significantly impaired visual texture recognition but with intact visuoperceptual functions, except contrast sensitivity. Using an optimal cut-off score according to the receiver operating characteristic (ROC) curve analysis, the results from the visual texture recognition of images could differentiate DLB patients from controls with a sensitivity of 92% and a specificity of 97%. Conclusions: We demonstrated significantly impaired visual texture recognition in patients with DLB and AD, with patients with DLB performing significantly worse than patients with AD. Additionally, visual texture recognition and visuoperceptual functions are independently disturbed in DLB.